2012
DOI: 10.19030/tlc.v9i3.7086
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing The Quality Of Teaching And Learning Through Action Research

Abstract: In every society, a great deal is expected from teachers. They

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
(35 reference statements)
2
10
0
1
Order By: Relevance
“…Since in the field of education, teachers categorically become researchers in an action research, it has always been linked to teacher's professional development (Hine, 2013;Stewart, 2013;Mahani, 2012;West, 2011;Cain and Milovic, 2010). This is mainly because teachers get to try new teaching pedagogies that work best in their respective classrooms, evaluate teaching materials and design a new curriculum program for the school (O'Connor, et.at, 2006;Ulla, 2017).…”
Section: Teachers' Perceptions In Doing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in the field of education, teachers categorically become researchers in an action research, it has always been linked to teacher's professional development (Hine, 2013;Stewart, 2013;Mahani, 2012;West, 2011;Cain and Milovic, 2010). This is mainly because teachers get to try new teaching pedagogies that work best in their respective classrooms, evaluate teaching materials and design a new curriculum program for the school (O'Connor, et.at, 2006;Ulla, 2017).…”
Section: Teachers' Perceptions In Doing Researchmentioning
confidence: 99%
“…Much has been written about the importance of action research in teacher education (Hine, 2013;Hong & Lawrence, 2011;Young, Rapp, Murphy, 2010;Vogrinc & Zuljan, 2009;Hien, 2009) and its effect to quality classroom instruction (Mahani, 2012;O'Connor, Greene & Anderson, 2006). The belief that teachers are active participants towards the development of education shows that by knowing the problem in the classroom; and by taking an action regarding that problem, teachers become the catalysts for change and responsible agents for the improvement of their own classroom teaching and for uplifting students learning.…”
Section: Introductionmentioning
confidence: 99%
“…At the K-12 level, research is often discussed as personal or collaborative reflection to delineate educational outcomes [1315]. According to some authors, action research in higher education makes the research more applicable to the real world through combining research and practice [16, 17]. In 2005, Herr and Anderson [18] described how action research proposals and dissertations are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Two, it serves as an opportunity for educators to self-evaluate their teaching practices (Hong and Lawrence, 2011) [4]. Three, it allows teachers to make a change in their pedagogical practices that will have a positive impact upon teaching and learning (Mahani, 2012) [5].…”
mentioning
confidence: 99%
“…However, despite its positive effects upon classroom teaching and learning, a number of studies have reported some factors that prevent teachers from doing research. Crowded teaching timetables, heavy teaching workloads (Kutlay, 2013;Morales, 2016) insufficient research training (Ellis &Loughland, 2016) [6], lack of research skills (Vasquez, 2017), lack of financial support (Biruk, 2013) and limited time to do research (Norasmah& Chia, 2016) [7] often constitute the primary challenges and concerns faced by teachers and other educators aspiring to undertake research.…”
mentioning
confidence: 99%